Process Skills in Mathematics Learning - Yantoro, Yantoro; Syahrial, Syahrial; Perdana, Rahmat; Citra, Yulita Dwi (Journal of Education Reseach and Evaluation, 2022)
The process skills possessed by students are currently still relatively low. This problem must be found to find out how the process skills possessed by students are. This study measures the skills of students in four schools. The purpose of this study was to describe students' process skills in each school and to determine the differences in the students' process skills in each school. This study uses quantitative research with survey research procedures. The number of samples is 140 samples. The instrument used in this research is a process skill observation sheet that an expert validator has validated. This study uses data analysis techniques in the form of descriptive statistical analysis tests and inferential statistical analysis tests. The research results on student skills can be categorized as good to very good. Good on all four indicators. Through research, it is also known that there are significant differences between process skills and there are significant differences between skills. The positive impact that teachers can feel is knowing how the process skills possessed by students in their schools are.